Electrolytic polishing of compacted graphite iron for revealing subsurface graphite of honed cylinders - Vale,João Luiz do (2019)
ABSTRACT The superficial characteristics of honed surfaces are relevant for the tribological performance of cylinders of internal combustion engines (MCI). Recent studies found a correlation between the occurrence of the phenomenon called folded metal and the presence of graphite of cast irons. However, the honing process tends to overlap the graphite, such that an application of a technique to remove a thin layer of material, exposing the graphite, would be useful. This paper aims to determine the best condition, of electric potential and time, for the exposition of graphite in honed surfaces using a technique of electrolyte polishing. The polishing was made on the concave surface with aid of a polishing mask developed for this matter. Samples of honed cylinders were removed from MCI manufactured using a compacted graphite iron. The characterizations were done through metallography and white light interferometry. To determine the ideal condition, several conditions of polishing were tested. For the verification of the repeatability, five repetitions were performed with the best condition. The results showed satisfactory repeatability, with an exposition of graphite and the matrix etching. The roughness of the polished region presented considerable uniformity, with a significant change of roughness in comparison to the honed surface. Furthermore, removal of the characteristic topography of the honed surface was observed. The layer removed showed little variation in depth along the polished region, with values close to 5 µm. This value accomplishes the demand of layer removal for the exposition of subsurface graphite.